Secrets of Silicon Valley : What Everyone else can Learn from the Innovation Capital of the World - Piscione, Deborah Perry (New York Palgrave Macmillan, 2013)
In Secrets of Silicon Valley, entrepreneur and media commentator Deborah Perry Piscione takes us inside this vibrant ecosystem where meritocracy rules the day. She explores Silicon Valley's exceptionally risk-tolerant culture, and why it thrives despite the many laws that make California one of the worst states in the union for business.
Include Illustrations, Notes and Index.
What Everyone else can Learn from the Innovation Capital of the World.
Keywords: Economic history -- High technology industries -- Technological innovations -- California--Santa Clara County -- New business enterprises